2014
DOI: 10.2131/jts.39.775
|View full text |Cite
|
Sign up to set email alerts
|

Early indicators of delayed adverse effects in female reproductive organs in rats receiving neonatal exposure to 17alpha-ethynylestradiol

Abstract: -We previously reported that neonatal exposure to 17α-ethynylestradiol (EE) led to delayed adverse effects in which age-related anovulation after sexual maturation was accelerated. To identify early indicators of these adverse effects, female Wistar Hannover GALAS rats received a single EE injection (0, 0.02, 0.2, 2, 20, or 200 μg/kg) within 24 hr of birth. Histopathological changes in ovarian and uterine development were investigated from postnatal day (PND) 14 to 10 weeks of age. Immunohistochemical expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Previously, it has been reported that ERα expression was down‐regulated in both MPN and VMHvl in neonatal BPA‐exposed females (Monje et al, ). Using a similar protocol to that herein, a single neonatal ≥0.02 μg kg −1 EE‐treated female rats decreased ERα expression in the uterine epithelium at oestrus in a dose‐dependent manner (Takahashi et al, ). In addition, single neonatal exposure to 2 (HEE) and 0.02 mg kg −1 (LEE) EE decreased ERα expression in the hippocampus of adult female rats (Shiga et al, ), an effect also expected to occur in the hypothalamus.…”
Section: Discussionmentioning
confidence: 89%
“…Previously, it has been reported that ERα expression was down‐regulated in both MPN and VMHvl in neonatal BPA‐exposed females (Monje et al, ). Using a similar protocol to that herein, a single neonatal ≥0.02 μg kg −1 EE‐treated female rats decreased ERα expression in the uterine epithelium at oestrus in a dose‐dependent manner (Takahashi et al, ). In addition, single neonatal exposure to 2 (HEE) and 0.02 mg kg −1 (LEE) EE decreased ERα expression in the hippocampus of adult female rats (Shiga et al, ), an effect also expected to occur in the hypothalamus.…”
Section: Discussionmentioning
confidence: 89%
“…However, it has been clearly established that the kisspeptin neuroendocrine network is highly dependent on gonadal steroids during postnatal development (Clarkson et al, 2009a ), and there is some growing evidence for the susceptibility of the kisspeptin neuroendocrine network to environmental pollution during the postnatal period (Franceschini and Desroziers, 2013 ). In female rats, perinatal exposure to 5, 15, or 50 μg/kg/d EE2 did not induce significant changes in kiss-1 mRNA levels in adulthood (Overgaard et al, 2013 ), as Takahashi et al ( 2014 ) found that a single injection of a low dose of 0.02 μg/kg EE2 at PND1 decreased hypothalamic Kiss-1 mRNA levels at PND14. In the present study, kisspeptin immunoreactivity was investigated in the PVpo, but not in the anteroventral periventricular (AVPV) nucleus or arcuate nucleus (Clarkson et al, 2009b ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory also identified that the rat neonatally exposed to various dose of EE showed the decreased FSH levels at PND14 and decreased ER␣ expression in the uterine epithelium at 10 weeks of age [44]. These early stage functional changes in the kisspeptin neuron, hormone balance and reproductive tissues might have the possibility to be the useful indicator for the delayed effects substitute for the abnormal estrous cycle occurred in later age, and may provide a new clue for the further investigation and risk identification of the delayed effect induced by the estrogenic chemicals like EDCs.…”
Section: Discussionmentioning
confidence: 95%